PENGARUH METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA PADA KONSEP KOPERASI DAN PENGELOLAAN KOPERASI KELAS X DI SMAN 11 KOTA PEKANBARU - Harni Lasri; Gimin '; RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was conducted at SMAN 11 Pekanbaru with the aim to analyze problem solving method to student learning outcomes. The population in this study were students of class X IPS and Samples performed by using simple random sampling because the samples taken 2 classes based on homogeneity test results from the class. Technique of completion of data is done by observation, documentation and teacher activity sheet then the data is analyzed using homogeneity test test and t test. The result of the research shows that the result of pretest of X class students still get very less category and the result of pretest result of students is done by determining homogenous class with simple random sampling technique and can be homogenous class group that is class X IIS 2 and X IIS 4 Levene's test results 0.819> 0.05 which means that the data comes from a homogeneous variant. After doing the pretest then the homogenity test is done postes The data obtained from the experimental class postes and control classes will be analyzed using levent test. Then get value Pvalue 0,743> 0,05 then this can be interpreted that data of learning result of postest class of IIS 4 and X IIS 2 is homogeneous. After the homes of postes test, then t test analysis from post test of experiment class and control class with 5% (α 0,05) belief obtained significance value 0,007 so it can be interpreted that there is significant difference.Keywords: Problem Solving Method, Student Learning Results